Sleep Quality Among Teenagers and Young Adults With Cancer. Issue 1 (January 2021) - Fortmann, Judith; Fisher, Abigail; Hough, Rachael; Gregory, Alice; Pugh, Gemma
Abstract : Background: Teenagers and young adults (TYAs) with cancer are known to suffer poor sleep quality and sleep disturbances; understanding the level of burden is essential to improving patient outcomes via supportive care interventions. Objectives: To compare sleep quality and the prevalence of sleep disturbances among TYA cancer patients, TYA survivors, and general population TYAs with no history of cancer. Methods: Teenager and young adult patients receiving active cancer treatment (n = 70), TYA cancer survivors (n = 151), and general population TYAs (n = 324) aged between 13 and 24 years completed the Pittsburgh Sleep Quality Index. Analyses of covariance were used to investigate potential group differences. Age at survey diagnosis, gender, ethnicity, and health status were included as covariates. Results: 84.29% of TYA patients, 62.91% of TYA cancer survivors, and 65.12% of general population TYAs reported Pittsburgh Sleep Quality Index scores greater than 5, suggesting clinically significant sleep disorders. Teenager and young adult patients reported significantly poorer global sleep quality compared with TYA survivors (mean difference, 0.99; 95% confidence interval, 0.03–1.96; P = .044) and general population TYAs (mean difference, 1.34; 95% confidence interval, 0.26–2.41; P = .009). Teenager and young adult patients and survivors reported significantly poorer sleep latency ( P = .003 for TYA patients, P = .035 for TYA survivors off treatment) and habitual sleep efficiency ( P < .001 for TYA patients, P = .014 for TYA survivors) than general population controls. Conclusions: The significant differences observed suggest young people with cancer, particularly those on treatment, may benefit from specialized sleep interventions. Implications for Practice: Efforts to ensure health professionals have the knowledge and skills to provide advice about sleep to young people with cancer are needed.